2023
DOI: 10.3390/medicina59071240
|View full text |Cite
|
Sign up to set email alerts
|

Calprotectin, Biomarker of Depression in Patients with Inflammatory Bowel Disease?

Abstract: Background and Objectives: Calprotectin is a marker for intestinal inflammation. Recent research suggests a link between inflammation and depression. This study assessed the association between the levels of calprotectin in patients from South-Eastern Europe and the severity of depression, anxiety, and quality of life. Materials and Methods: This cross-sectional study included 30 confirmed patients with Crohn’s disease (CD) and ulcerative colitis (UC) who were assessed using clinical interviews for determining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Asscher et al found no difference in the proportion of abnormal GDS scores between their groups (which they confirmed in a sensitivity analysis using ≥ 50µg/g and <50 µg/g to define high and low FC groups respectively) [18]. Iordache and colleagues offered a novel insight, correlating absolute FC concentration with questionnaire scores in order to determine the ideal threshold for detection of clinical depression [14]. Here, Iordache et al reported that a cut-off of 131 µg/g or higher could potentially be used to predict clinical depression, having a sensitivity of 82%, specificity of 61%, and accuracy of 70% in their sample population [14].…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Asscher et al found no difference in the proportion of abnormal GDS scores between their groups (which they confirmed in a sensitivity analysis using ≥ 50µg/g and <50 µg/g to define high and low FC groups respectively) [18]. Iordache and colleagues offered a novel insight, correlating absolute FC concentration with questionnaire scores in order to determine the ideal threshold for detection of clinical depression [14]. Here, Iordache et al reported that a cut-off of 131 µg/g or higher could potentially be used to predict clinical depression, having a sensitivity of 82%, specificity of 61%, and accuracy of 70% in their sample population [14].…”
Section: Discussionmentioning
confidence: 95%
“…Out of the studies selected, the scales used to assess depression were the Patient Health Questionnaire (PHQ-9) [14,15,19], the Hamilton Depression Rating Scale (HDRS24/HAM-D) [21,22], the Geriatric Depression Scale (GDS) [18], and the Hospital Anxiety and Depression Scale (HADS-D) [20]. All these scales are validated for assessing depression severity in clinical settings [23][24][25][26].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations